Seed harvest from medicinal fennel, Foeniculum vulgare Mill, in desert areas - Kholturaev Sharofiddin Chorievich; Ruzmetov Umid Ismailovich; Khofizov Bakhriddin Turdievich; Ulugova Safargul Fayzullaevna (Caspian Journal of Environmental Sciences)
In this study, the spread of the medicinal fennel, Foeniculum vulgare Mill, government decisions on propagation, as well as the development of optimal agricultural technologies for the cultivation of medicinal fennel were assessed. In addition, the research on the number of branches of fennel, the number of flowers and the length of the roots of the fertilizers used in the studies were conducted at the end of 2018. The norms of N20P60K40, N40P60K40 and N60P60K40 were applied to obtain high quantity and quality seeds. The optimal amounts were determined and the information was cited.